PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE JIGSAW DI SEKOLAH DASAR - Irawan, Rudi; Mansurdin, Mansurdin; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to improve student learning outcomes in IPS learning with the model Cooperative Learning Type Jigsaw in grade V elementary school. The type of this research is Classroom Action Research (PTK). The results of the first cycle of research on average RPP 75% (C), increased in cycle II to 92,8% (SB). Implementation of cycle I on teacher aspect average 76% (C), increase in cycle II to 95,8% (SB). The implementation of cycle I in student aspect averaged 72,9% (C), increased in cycle II to 95,8% (SB). Student learning outcomes in cycle I average 76,5, increased in cycle II to 84,1. Thus, Model Cooperative Learning Type Jigsaw can improve student learning outcomes in IPS learning.Keywords: Learning Outcomes, Social Studies, Model Cooperative Learning Tipe Jigsaw